الشرق الأوسط الجديد وصراع المحاور - ثامر, محمد عبد الرؤوف; شنوف, صهيب (جامعة الوادي University of Eloued, 2019)
ملخص: تعالج هذه الدراسة تشكيل الشرق الأوسط الجديد عبر عديد المحطات التاريخية منذ بروز الحركة الصهيونية، التي راحت تستدرج عدة قوى دولية لخدمة مشروعها الاستيطاني و باعتبارها العنصر و العامل المؤثر لإرساء معالم القرن الواحد والعشرين بمفهوم جديد للشرق الاوسط، وقد استفادت من الخدمة البريطانية بداية من اصدار وعد بلفور1917 وهذا ما كان يتماشى مع مختلف المشاريع الاستعمارية التي طالت المنطقة العربية لعل اهمها مشروع كامبل بنرمان 1905القاضي بزرع كيان اجنبي في قلب الامة العربية، لتتوالى المشاريع والمخططات على حساب المنطقة، ضمن صياغة جديدة للشرق الاوسط، وفي كل مرة تجد هذه المخططات والمشاريع ردود افعال عربية متباينة. فدخلت الأمة العربية أتون حروب متتالية في مواجهة الكيان الصهيوني كمحور اساسي ضمن محاور الصراع وبدعم بريطاني ثم امريكي منذ منتصف القرن العشرين الى اوائل القرن الحادي والعشرين. وفي كل مرة تظهر محاولات جديدة لإعادة صياغة الشرق الاوسط وفق التوجهات الامريكية. ومنه يمكن الوصول الى دور محاور الصراع امريكا والكيان الصهيوني وبريطانيا والطرف العربي في تشكيل منطقة الشرق الاوسط الجديد. الكلمات المفتاحية: فلسطين- لبنان-الشرق الأوسط الجديد-الحروب العربية الصهيونية –سوريا. Abstract: .This study deals with the formation of the new Middle East through several historical stations since the rise of the Zionist movement, which has been attracting several international forces to serve its settlement project. As being the most influential factor for establishing the features of the twenty-first century with a new concept of the Middle East, it benefited from British support starting with the issuance of the Balfour Declaration of 1917, which was in line with the various colonial projects that affected the Arab region such as Campbell Penerman project in 1905 to plant a foreign entity in the heart of the Arab nation. Colonial projects continued at the expense of the region, within a new formulation of the Middle East, and each time these projects received different reactions from the Arabs. The Arab nation entered successive wars against the Zionist entity as part of the conflict with them backed by British and American support from the middle of the twentieth century to the early twenty-first century. Every time there are new attempts to reformulate the Middle East according to American orientations. Hence, we can identify the main axes of this conflict for the formation of the new Middle East, namely, America, the Zionist entity, and Britain on one part, and the Arabs on the other part. key words: Palestine-Lebanon-the new Middle East-the Israeli-Arab wars-Syria.
The New Middle East And The Axis Conflict
Keywords: فلسطين، لبنان، الشرق الأو سط الجديد، الحرو ب العربية الصهيونية، سوريا; palestine-Lebanon- the new Middle East-the Israeli-Arab-Syria